The Role of Patience and Gratitude in Shaping a Student's Noble Morals - Mohammad Ainun Najib; Yusuf Sufandi; Isna Alvinatu Reza (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the declining trend in the quality of students' morals amidst the rapid development of technology and the flow of globalization, while studies on patience and gratitude as the basis of hadith-based character education are still limited to the context of certain educational institutions and have not yet conducted in-depth dialogues between hadith texts and the challenges of education in the digital era. Previous studies generally discuss patience or gratitude separately at certain levels or institutions, so they have not produced a conceptual synthesis that fully connects these two values ​​as the foundation of student morals. This study aims to analyze the values ​​of moral education contained in the hadith of the Prophet Muhammad ﷺ about patience and gratitude and examine their relevance to the formation of student character from the perspective of contemporary Islamic education. The study uses a qualitative approach of the library type by collecting, classifying, and analyzing hadiths about patience and gratitude along with their explanations, then dialogues them with character education literature through content analysis techniques. The results of the study indicate that hadiths about patience teach self-control and perseverance, while hadiths about gratitude teach appreciation for even the smallest blessings, and these two values ​​complement each other in shaping students' personalities to be resilient, humble, and adaptive in facing the challenges of education in the digital era. This study contributes an integrative conceptual framework of patience and gratitude based on hadith that can serve as a reference for developing moral education strategies in schools and madrasas